Laboratory manual and workbook in microbiology : - Morello, Josephine A. (McGraw-Hill Higher Education, 2006)
This laboratory manual and workbook, now in its Eighth Edition, maintains its original emphasis on the basic principles of diagnostic microbiology for students preparing to enter the allied health professions. It remains oriented primarily toward meeting the interests and needs of those who will be directly involved in patient care and who wish to learn how microbiological principles should be applied in the practice of their professions.